Analisis Sistem Pemilu Proporsional Dan Dampaknya Terhadap Representasi Politik Perempuan di Indonesia - Revian Jedha Arhansyah; Nadhil Najwan Putra Cahya; Muhamad Febri Pribadi; Ifyar Aztyardi Anhar (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
This research highlights the importance of women's representation in the legislature as an indicator of the quality of democracy in Indonesia. Although regulations set a minimum quota of 30% women's representation, the realization is still low with a projection of only 22.1% of women elected in the 2024 DPR. The open proportional electoral system provides opportunities but also presents challenges, such as money politics and patriarchal culture. Internal factors such as lack of confidence and double burden, as well as external factors such as political violence and lack of support from parties, hinder women in politics. To increase this representation, strategies such as gender mainstreaming in political communication, effective affirmative action, and inclusive political education are needed. These efforts aim to create a more inclusive and gender-equal parliament, supporting women's role in public policy-making.